STUDI KOMPARATIF KUALITAS PELAYANAN BELLBOY DI HOTEL AXANA PADANG DALAM MELAYANI TAMU INDIVIDU DAN TAMU GRUP - Fikri Adib Putra (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2018)
STUDI KOMPARATIF KUALITAS PELAYANAN BELLBOYDI HOTEL AXANA PADANG DALAM MELAYANITAMU INDIVIDU DAN TAMU GRUPFikri Adib Putra1,Ira Meirina Chair2Program Studi D4 Manajemen PerhotelanJurusan PariwisataFPP Universitas Negeri Padangemail: fikriadib33@gmail.comAbstract. This study aims to describe and compare service quality by bellboy at The Axana Hotel Padang. The research is quantitative descriptive with a comparative approach. The sample used was purposive sampling which was 189 individual guests dan group guests who had stayed at The Axana Hotel Padang, using a questionnaire with a likert scale that had been tested for validity and reliability. Data analysis techniques using statistical tests with Chi Square. The result obtained are as follows: (1) The service of quality by bellboy in serving individual guests at The Axana Hotel Padang Hotel obtained an average score of 3.00 with a good category. (2) The service of quality by bellboy in serving group guests at The Axana Hotel Padang obtained an average score of 3.02 with a good category. (3) Comparison of service quality by bellboy in serving individual guests and group guests at The Axana Hotel Padang shows the results of the test analysis obtained by P value (0.000< 0.05 Ho hypothesis is refused. That means there is difference in the service of quality by bellboy at The Axana Hotel Padang Hotel in serving individual guests and group guests.Keywords: Service of Quality, Bellboy, Comparative Study